Ostéotomie de Gauthier et fixation par ostéo-sutures dans le traitement de la maladie de Freiberg - Daoudi, Ahmed (Pan Afr Med J, 2018)
Freiberg’s disease is an osteochondrosis of the metatarsal heads mainly affecting the second metatarsal head. This study was conducted over a 3 year period. It reports 6 cases of patients, whose average age was 19.8 years, who had undergone Gauthier’s dorsal subtraction osteotomy with fixation using osteosutures. The outcome of this technique was satisfactory. Indeed, the majority of patients had no pain and recovered normal daily activity. This study highlights that fixation using osteosutures is a reliable and inexpensive method.